Genetic data and the law : a critical perspective on privacy protection - Taylor, Mark, 1973 Mar. 26- (Cambridge : Cambridge University Press, 2012)
'Research using genetic data raises various concerns relating to privacy protection. Many of these concerns can also apply to research that uses other personal data, but not with the same implications for failure. The norms of exclusivity associated with a private life go beyond the current legal concept of personal data to include genetic data that relates to multiple identifiable individuals simultaneously and anonymous data that could be associated with any number of individuals in different, but reasonably foreseeable, contexts. It is the possibilities and implications of association that are significant, and these possibilities can only be assessed if one considers the interpretive potential of data. They are missed if one fixates upon its interpretive pedigree or misunderstands the meaning and significance of identification. This book demonstrates how the public interest in research using genetic data might be reconciled with the public interest in proper privacy protection'--
Introduction -- Privacy -- Genetic data -- The law -- Data in common -- Anonymity -- Human tissue -- Genetic discrimination -- Potential, promise and possibility.
Includes bibliographical references and index.
Keywords: Medical genetics -- Law and legislation; Medical records -- Access control; Genetic engineering -- Law and legislation; Biotechnology -- Law and legislation; Human chromosome abnormalities -- Diagnosis -- Law and legislation; Human genetics -- Government policy; Privacy, Right of; Data protection -- Law and legislation